Naturally Acquired Antibody Response to Malaria Transmission Blocking Vaccine Candidate Pvs230 Domain 1 - Tentokam, Bergeline C. Nguemwo; Amaratunga, Chanaki; Alani, Nada A. H.; MacDonald, Nicholas J.; Narum, David L.; Salinas, Nichole D.; Kwan, Jennifer L.; Suon, Seila; Sreng, Sokunthea; Pereira, Dhelio Batista; Tolia, Niraj H.; Fujiwara, Ricardo T.; et al. (Frontiers in Immunology, 2019)
Plasmodium vivax malaria incidence has increased in Latin America and Asia and is responsible for nearly 74.1% of malaria cases in Latin America. Immune responses to P. vivax are less well characterized than those to P. falciparum, partly because P. vivax is more difficult to cultivate in the laboratory. While antibodies are known to play an important role in P. vivax disease control, few studies have evaluated responses to P. vivax sexual stage antigens. We collected sera or plasma samples from P. vivax-infected subjects from Brazil (n = 70) and Cambodia (n = 79) to assess antibody responses to domain 1 of the gametocyte/gamete stage protein Pvs230 (Pvs230D1M). We found that 27.1% (19/70) and 26.6% (21/79) of subjects from Brazil and Cambodia, respectively, presented with detectable antibody responses to Pvs230D1M antigen. The most frequent subclasses elicited in response to Pvs230D1M were IgG1 and IgG3. Although age did not correlate significantly with Pvs230D1M antibody levels overall, we observed significant differences between age strata. Hemoglobin concentration inversely correlated with Pvs230D1M antibody levels in Brazil, but not in Cambodia. Additionally, we analyzed the antibody response against Pfs230D1M, the P. falciparum ortholog of Pvs230D1M. We detected antibodies to Pfs230D1M in 7.2 and 16.5% of Brazilian and Cambodian P. vivax-infected subjects. Depletion of Pvs230D1M IgG did not impair the response to Pfs230D1M, suggesting pre-exposure to P. falciparum, or co-infection. We also analyzed IgG responses to sporozoite protein PvCSP (11.4 and 41.8% in Brazil and Cambodia, respectively) and to merozoite protein PvDBP-RII (67.1 and 48.1% in Brazil and Cambodia, respectively), whose titers also inversely correlated with hemoglobin concentration only in Brazil. These data establish patterns of seroreactivity to sexual stage Pvs230D1M and show similar antibody responses among P. vivax-infected subjects from regions of differing transmission intensity in Brazil and Cambodia.